Cytokine, catabolic enzyme and structural matrix gene expression in synovial fluid following intra‐articular administration of triamcinolone acetonide in exercised horses. (8th January 2016) - Knych, H. K.; Vidal, M. A.; Chouicha, N.; Mitchell, M.; Kass, P. H.
Summary: Reason for performing study: The frequent use of intra‐articular triamcinolone acetonide (TA) in performance horses warrants further study of the duration of as well as the beneficial and detrimental effects on gene expression associated with administration. Objectives: To assess the effects of intra‐articular administration of TA on the expression of selected anti‐ and proinflammatory and structural matrix genes following its administration into joints of exercised Thoroughbred horses and to correlate these effects with plasma and synovial fluid drug concentrations. Study design: Block design experiment. Methods: Eight exercised horses received a single intra‐articular administration of 9 mg of TA. Synovial fluid samples were collected from the treated and contralateral joints prior to and up to 49 days following drug administration. Microarray and quantitative reverse transcription polymerase chain reaction analysis were used to assess changes in expression levels of various inflammatory and structural genes post drug administration. Results: Drug concentrations in plasma and synovial fluid, were no longer quantifiable by 6 and 28 days following drug administration respectively. In total, the expression level of 5490 genes were significantly altered on micro array analysis, following intra‐articular TA administration. Of the genes selected for further study by quantitative reverse transcription polymerase chain reaction analysis, significant changes in inflammatory genes (annexin type 1, cyclooxygenase‐1 and tumour necrosis factor stimulated gene 6) and structural genes (collagen and aggrecan) were noted. Conclusions: This study supports the use of synovial fluid as a biological matrix for studying the effects of corticosteroids on gene expression. For the majority of genes studied the effects on expression relative to baseline for both inflammatory and matrix genes were prolonged relative to plasma and synovial fluid TA concentrations. Downregulation of collagen gene expression warrants the careful use of TA in horses.